VISIT-TO-VISIT GLOMERULAR FILTRATION RATE VARIABILITY AS A PREDICTOR FOR CARDIOVASCULAR AND RENAL OUTCOMES IN ESSENTIAL HYPERTENSION: DATA FROM A GREEK 8-YEAR-FOLLOW-UP STUDY. (April 2021) - Laina, A.; Tsioufis, K.; Dimitriadis, K.; Kasiakogias, A.; Liatakis, I.; Koutra, E.; Leontsinis, I.; Konstantinidis, D.; Kouremeti, M.; Dri, E.; Iliakis, P.; Vogiatzakis, N.; et al.
Abstract : Objective: Renal dysfunction is related with adverse prognosis in hypertension, however scarce data exist on the predictive value of kidney function variability on cardiovascular and renal outcomes in this setting. This study aims to assess the prognostic role of visit-to-visit glomerural filtration rate (GFR) variability on the incidence of coronary artery disease (CAD), stroke and end-stage renal disease in hypertensive patients. Figure. No caption available. Design and method: We followed 2380 essential hypertensives (mean age 58.9 years, 1240 males, office blood pressure 144/91mmHg) free of cardiovascular disease for a mean period of 8 years. All subjects had at least one annual visit and blood sampling was performed in all visits for GFR estimation. We calculated standard deviation (SD) of mean GFR from visits 6months onward in patients with >or = 5 visits during follow-up. CAD was defined as the history of myocardial infarction or significant coronary artery stenosis revealed by angiography or coronary revascularization procedure, while stroke was defined as rapid onset of a new neurological deficit persisting at least 24 hours unless death supervened confirmed by imaging findings. End-stage renal disease was defined as GFR<15 mL/min/1.73 m2 or the need for long-term dialysis or transplantation. Results: The incidence of CAD, stroke and end-stage renal disease over the follow-up period were 2.8% (n = 68), 1.09% (n = 26) and 0.6% (n = 14). Hypertensives who developed CAD (n = 2312) had at baseline higher left ventricular mass index (115.7 ± 24.6 vs 103.7 ± 27.3 g/m2, p < 0.0001) compared to those who did not, whereas there was no difference with respect to baseline GFR (78 ± 19.6 vs 79.3 ± 18.6 mL/min/1.73 m2 (p = 0.573). In multivariate Cox regression models visit-to-visit glomerular filtration rate predicted end-stage renal disease (hazard ratio = 1.758, p = 0.01) but not CAD and stroke (p = NS for both). Baseline left ventricular mass index independently predicted CAD (hazard ratio = 1.042, p = 0.015) and stroke (hazard ratio = 1.035, p = 0.002). Conclusions: In essential hypertensive patients GFR variability predicts future development of end-stage renal disease but exhibits no independent prognostic value for CAD and stroke. These results suggest that fluctuations of renal function are related with damage at the kidneys and not at the cardiac and cerebrovascular level.